Архитектурная модель библиотеки рефлексии для неуправляемого C++ - Михтонюк, С. В.; Приходченко, Р. С. (ХНУРЭ, 2009)
A reflection mechanism, available under most managed languages, allows to greatly facilitate the solution of several classes of problems connected with parsing and scripting. This article discusses architectural concerns of an implementation of reflection library in native C++ that allows saving of metalevel information about program structure up to the program runtime.